Gaza preparing for dawn - Macintyre, Donald (Oneworld Publications, 2018)
Uniquely imprisoned, most Palestinians in Gaza cannot travel beyond the confines of the Strip, and in times of war escape is impossible. They live under siege - economic and armed - and yet so many remain courageous, outspoken and steadfast. Donald Macintyre lays bare Gaza's human tragedy and reveals how it became a crucible of conflict and a byword for suffering. He identifies the repeated failings - including those of the international community - that have seen countless opportunities for peace pass by. Yet, against all odds, hope for a better future lingers. Gaza was once a flourishing coastal civilization open to the world. Could it be so again?